Research on Chinese Journalists' Scientific Literacy - Hu, Xiao Juan (Frontiers in Communication, 2022)
Journalists are always on the “second battlefield” of fighting against COVID-19. In the face of major public health events, their scientific literacy is directly related to the effect of emergency science popularization. Based on related surveys and interview data in China, this article reviews the research on journalists' scientific literacy, clarifies the value of scientific literacy in journalism, and analyzes the cognition and practice of journalist scientific literacy. Through the analysis of cognition and practice, it explores feasible ways to effectively improve scientific literacy. The study found that journalist scientific literacy has a unique value in the crisis period, but the real measurement and self-cognition are not high. In the post-epidemic era, the social construction of science communication is stronger, and the media need to achieve a high degree of interaction with the scientific community to transform authoritative knowledge into popular science. Journalists should improve scientific literacy from their learning and professional training while using new media technology to scientifically demonstrate information.